Gaharu Sensor: Classification using Case Based Reasoning (CBR) - Muhamad Faruqi, Zahari; M. S., Najib; Kamarul Hawari, Ghazali; Fathimah, Abdul Halim; Saiful Nizam, Tajuddin; Erny Haslina, Abd Latib (Penerbit UMP, 2016)
Agriculture was an important industry, which has an economic impact of trading goods for others application such as perfume, aromatherapy and others. Agar wood one of high value products that give economic impact for several of the countries which price of agar wood to its certain grade. The grades were manipulated by traders to get higher price using lower grade. This paper proposed the intelligence classification technique using an Electronic Nose (E-nose) measurement. The sensor array in the E - nose are used for the inputs of the Case Based Reasoning (CBR) for intelligent classification. The experimental result shows that the technique accomplished to classify with high accuracy which is 96.3% nearly to 100% of accuracy.